Study on the gut microbiota, HPA, and cytokine levels in infantile spasms - You, Jiajia; Liu, Li; Pan, Xiongfeng; Wu, Liwen; Tan, Lihong; Zhou, Changci; Fang, Siwei; Xiao, Zhenghui; Qiu, Jun (Frontiers in Immunology, 2024)
Objective The mechanisms driving the progression of infantile spasms are not well understood. We aimed to investigate the changes and correlations of the gut microbiota, the hypothalamus–pituitary–adrenal (HPA) axis hormones, and the inflammatory cytokines in children with infantile spasms before and after treatment in order to provide a reference for future pathogenesis research. Methods Children with infantile spasms who were admitted to our hospital were recruited into the case group. The case group was divided into the pre-treatment group (group A, n = 14), the 2 weeks after treatment group (group B), and the 1 month after treatment group (group C). On the other hand, healthy children with the same sex ratio as the case group were recruited into the control group (group D, n = 14). Three stool and blood samples were collected before treatment, 2 weeks after treatment, and 1 month after treatment. The serum samples were analyzed using cytometric bead array (CBA), enzyme-linked immunosorbent assay (ELISA), and chemiluminescent immunoassay (CLIA) to measure the levels of HPA axis hormones and inflammatory cytokines. The collected stool samples were sequenced using 16S rDNA. Results The pre-treatment group demonstrated elevated levels of corticotropin-releasing hormone (CRH), interleukin 2 (IL-2), IL-4, IL-6, and IL-17α, which decreased with treatment. The level of CRH was lower in the effective group than that in the ineffective group. Sutterellaceae was lower in the pre-treatment group than that in the control group. Lachnospiracea_incertae_sedis was positively associated with CRH concentration (p < 0.05). After treatment, Sutterellaceae was negatively associated with IL-2 and TNF-α (p < 0.05). Conclusion This study found that imbalance of the gut microbiota may be involved in the pathogenesis of infantile spasms and is related to the response to adrenocorticotropic hormone (ACTH). Lachnospiraceae and Lachnospiracea_incertae_sedis might be involved in the disease onset. Sutterellaceae might have a link to children’s improved health.